Effectiveness of a Teaching Strategy Based on Transformative Learning Theory in Divergent Thinking Skills of Fourth-Grade Science Students in Mathematics - Al-Kubaisi, Marwa Ibrahim Rahim; Al-Maaiouf, Rafid Bahr Ahmed (Journal of Posthumanism, 2025)
This research aims to identify the effectiveness of a teaching strategy based on the Transformative Learning Theory in developing divergent thinking skills among fourth-grade science students in mathematics. A purposive sample was selected from a Preparatory School. Two sections (A and B) were randomly chosen, consisting of (42) students in the experimental group and (40) students in the control group. Equivalence between the two groups was established using the Otis-Lennon School Ability Test, and a divergent thinking skills test consisting of (15) items (prepared for the purpose of ensuring equivalence). A divergent thinking skills test was developed for the final application on the research sample (experimental and control groups) as a post-test. This test comprised (20) essay items. The validity and reliability of the test were verified, and statistical analyses were conducted. After the experiment concluded, the divergent thinking test was administered to both the experimental and control groups. The results indicated to difference at between degree average of the tow groups in the divergent thinking test, favoring the experimental group.